Laseman Hand-Drawn Batik Motifs and Socio-Religious Life Patterns of The Lasem Community - Jaeni, Muhammad; Hidayati, Nunung; Idris, Saliha (UIN Maulana Malik Ibrahim Malang, 2024)
Various Lasem batik motifs have been widely researched in Indonesia, but no one has researched the Lasem batik motifs using social semiotic analysis. The research aims to determine the meaning of Lasem batik motifs using a social semiotic analysis approach, understand the function of Lasem batik patterns and motifs, and determine their influence on the social life of the Lasem community. The approach used in this research is qualitative. The data collection methods used are observation, documentation, and in-depth interviews. The data analysis used in this research uses two types of analysis, namely content analysis and descriptive analysis. The results of the research explain that there are several meanings contained in Lasem's batik motifs, such as the meaning of togetherness, prosperity, caring, sincerity (not giving up), spreading goodness, rejecting evil, patience (holding back anger), and seriousness in living life. The use of batik is the style of the people who own it. Laseman Batik has experienced a shift in meaning and function. The transmission of values and meanings of batik motifs continues to be instilled in the community so that they become shared knowledge and can have implications for people's attitudes and behaviors among partners. Ragam motif batik Lasem telah banyak diteliti di Indonesia, namun belum ada yang meneliti motif batik Lasem ini dengan analisis semiotic social. Penelitian bertujuan untuk mengetahui pemaknaan motif batik Lasem dengan pendekatan analisis semiotic social, memahami fungsi corak dan motif batik Lasem serta mengetahui pengaruhnya terhadap kehidupan social masyarakat Lasem. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif. Metode pengumpulan data yang digunakan adalah pengamatan atau observasi, dokumentasi, dan wawancara mendalam. Analisis data yang digunakan dalam penelitian ini menggunakan dua jenis analisis yaitu analisis isi dan analisis deskriptif. Hasil penelitian menjelaskan bahwa Terdapat beberapa makna yang terkandung dalam motif-motif batik tulis Lasem, seperti: makna kebersamaan, kesejahteraan, kepedulian, kesungguhan (tidak putus asa), menyebar kebaikan, tolak bala, sabar (Menahan amarah), kesungguhan menjalani kehidupan. Penggunaan batik merupakan style masyarakat sebagai pemiliknya. Batik Laseman telah mengalami pergeseran makna dan fungsi. Transmisi nilai-nilai dan makna motif batik terus ditanamkan kepada masyarakat agar menjadi pengetahuan bersama dan pada gilirannya dapat berimplikasi kepada sikap dan perilaku masyarakat.